OPTIMIZING SOCIAL MEDIA ADVERTISING STRATEGIES: IDENTIFYING BEST PRACTICES INFLUENCING ONLINE BUYING BEHAVIOUR OF GENERATION Y - Dr. Kanchan Rani; Mr. Parvinder Singh Bajwa (IJRDO - Journal of Applied Management Science, 2026)
With the spread of social networks, the nature of commercial communication has shifted fundamentally, and digital advertising has become one of the key factors that influence the purchase behavior of the consumer. This paper is research of social media advertising best practices that will impact the online purchasing behavior of Generation Y consumers, and the sole sources of secondary data will be peer-reviewed empirical literature published within the past five years, 2020-2025, and industry reports by DataReportal, IBEF, TRAI, and UNCTAD. The methodology of thematic content analysis was used to synthesize the results of existing empirical works in a systematic manner in order to find convergent evidence on five dimensions of advertising: content creativity, message clarity, consumer engagement, influencer credibility, and call-to-action effectiveness. The results show that the strongest drivers of online purchase behavior among the Millennials are consistently reported to be consumer engagement and influencer credibility, then effective call-to-action design, message clarity, and content creativity. The results are theoretically supported by the Elaboration Likelihood Model and the Theory of Planned Behavior. The research adds a combined and supported framework of the knowledge of the social media advertising effectiveness among the generation Y consumers and this study is particularly applicable to the rapidly digitizing urban market in India.